Fish Lymphocytes: An Evolutionary Equivalent of Mammalian Innate-Like Lymphocytes? - Scapigliati, Giuseppe; Fausto, Anna M.; Picchietti, Simona (Frontiers in Immunology, 2018)
Lymphocytes are the responsible of adaptive responses, as they are classically described, but evidence shows that subpopulations of mammalian lymphocytes may behave as innate-like cells, engaging non-self rapidly and without antigen presentation. The innate-like lymphocytes of mammals have been mainly identified as γδT cells and B1-B cells, exert their activities principally in mucosal tissues, may be involved in human pathologies and their functions and tissue(s) of origin are not fully understood. Due to similarities in the morphology and immunobiology of immune system between fish and mammals, and to the uniqueness of having free-living larval stages where the development can be precisely monitored and engineered, teleost fish are proposed as an experimental model to investigate human immunity. However, the homology between fish lymphocytes and mammalian innate-like lymphocytes is an issue poorly considered in comparative immunology. Increasing experimental evidence suggests that fish lymphocytes could have developmental, morphological and functional features in common with innate-like lymphocytes of mammals. Despite such similarities, information on possible links between conventional fish lymphocytes and mammalian innate-like lymphocytes is missing. The aim of this review is to summarize and describe available findings about the similarities between fish lymphocytes and mammalian innate-like lymphocytes, supporting the hypothesis that mammalian γδT cells and B1-B cells could be evolutionarily related to fish lymphocytes.